Performance Comparison of PI Control and Fuzzy Logic for Speed Control of DC Shunt Motor Using Matlab / Simulink - Jehan Aliyya; Yahya Chusna Arif; Ony Asrarul Qudsi (Department of Electrical Engineering ITS and FORTEI, 2020)
DC motor speed regulation is an important role in the industrial process so it can run easily and efficiently. A good DC motor speed control system must have a fast and accurate response. However, it is rare to find a DC motor that has controlled to get a constant speed. This research presents an analytical comparison of PI controller and Fuzzy Logic Controller for Speed Control of DC Shunt Motor. The disadvantages of PI controller like it do not operate properly when the system has a high degree of load disturbances [1]. FLC is a good for load disturbances and can be easily implemented. The simulation of both speed controller have been made by Matlab Simulink software.Keywords: DC shunt motor, fuzzy logic control, matlab, PI control, simulink.